(untitled) (Research, Society and Development, 2022)
Herpes simplex virus type 1 (HSV-1) infection is considered common throughout the world and clinically manifests signs and symptoms in the oral region. The natural history of the disease comprises phases of primary infection, latency, and recurrent infection. Herpes labialis is the clinical manifestation of recurrent infection, characterized by small and numerous erythematous and painful papules, which constitute conglomerates of vesicles that rupture and form crusts. Among the therapeutic alternatives are antivirals, natural therapies and low-level laser therapy (TFBM). The present study aims to evaluate the effectiveness of TFBM in the treatment of herpes labialis lesions, through an integrative review of the literature. A research was performed for articles in the electronic databases MEDLINE via PubMed, LILACS via BVS, Web of Science and Cochrane Library published between 2011 and 2021 that addressed studies of cold sores with randomized clinical trials associating the descriptors “Low-intensity light therapy" OR "Photobiomodulation" OR "Laser" AND "Herpes Labialis", without language restriction. 60 studies were found, of which, after excluding duplicates and those that did not meet the inclusion criteria, 5 were selected for analysis. Therefore, the present review concludes that TFBM is an effective therapeutic resource, reducing healing time, symptoms and recurrence of lesions.